Implementation of Article 14 Paragraph 3 of the Regulation of the Regent of South Ogan Komering Ulu Number 23 of 2024 concerning the Provision of Parking Services on Public Roads from the Siyasah Tanfidziyyah Perspective (Study at the Kalangan Market, Banding Agung District, South Ogan Komering Ulu Regency) - Octari Listiana; Frenki Frenki; Mumhammad Jayus (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the implementation of Article 14 Paragraph (3) of South Ogan Komering Ulu Regency Regulation Number 23 of 2024 concerning the Provision of Parking Services on Public Roads and examine it from a siyasah fiqh perspective. The research method used was a qualitative method with a field research approach. Data were obtained through interviews with the Transportation Agency, market heads, parking attendants, and the public as parking service users, supported by secondary data from relevant literature. The results indicate that the implementation of the parking policy has been running quite well, indicated by the existence of a parking attendant legality system through a Decree (SK), the use of official barcode-based identification, and the provision of attributes as identification. Furthermore, the implementation of a deposit system with local governments serves as an indicator for determining parking legality. As of 2026, no significant reports of illegal parking or illegal levies were found. However, obstacles remain, such as incomplete parking attendant attributes and practices of evading supervisors. From a fiqh siyasah perspective, this policy reflects the principles of public interest, justice, and oversight (hisbah) in the management of public affairs. The government has fulfilled its role in maintaining order and preventing practices detrimental to the public. However, improvements in oversight and law enforcement are needed to ensure optimal and sustainable policy implementation.